Genetic Variability, Correlation, and Path Analysis in F2 Population of Sorghum - Rahayu, Anita; Wirnas, Desta; Trikoesoemaningtyas, Trikoesoemaningtyas; Reflinur, Reflinur (Journal of Tropical Crop Science, 2026)
Indonesian sorghum (Sorghum bicolor L.) germplasm with the highest genetic diversity can serve as a valuable resource for developing high-yielding cultivars. Therefore, the present research aimed to obtain information on genetic variability in the population and also determine the key traits associated with grain yield using correlation and path analysis in sorghum F2 population. The sorghum parental genotypes 'Demak 4' and 'Soraya 3', and a local high yielding IPB line, NS 19, NS 109, and NS 111, were used in the crosses. The F2 population was evaluated against parental cultivars and four check genotypes. The results showed that 64 individual plants were observed as transgressive segregants. Meanwhile, the number of leaves and plant height were controlled polygenically through additive genes. The traits of panicle diameter, dry panicle weight, and grain weight per panicle possessed the highest genotypic coefficient of variance. The traits dry panicle weight and diameter were significantly positively correlated with grain yield. The considerable positive correlation with dried panicle weight, panicle length, and diameter could be used as selection criteria. The path analysis reported that the observed agronomic traits explained 97.07% of the total variation in grain weight per panicle.